The Effect of Youtube Videos on Enriching The Vocabulary of The Eighth Grade Students of SMP N 3 Palembang - Erina Kiranti; Badriyah Ulfah; Desi Surayatika (CV. Ulil Albab Corp, 2022)
Vocabulary is an important thing in learning a foreign language, without mastery of vocabulary, we will have difficulty in learning a language because vocabulary is a basic aspect of language that must be mastered before mastering language skills. The use of video from YouTube which is interesting for students is certainly a special attraction to enrich vocabulary for students. This study used a quantitative method with quasi-experimental and nonequivalent control group design. The samples were class of VIII.5 as experimental group consisted of 33 students and class of VIII.6 as control group consisted of 33 students. Technique of collecting the data used pre-test and post-test. The data were analyzed by using t-test (paired sample and independent sample t-test) with SPSS v.25 program. The result of paired sample t-test in experimental group showed that t-obtained was 10,044 > t-table (df=32) was 2,036. Furthermore, the result of independent sample t-test showed that t-obtained was 0,1359 > t-table (df=64) was 1,997. It means that there was significant mean difference between experimental and control groups. The findings revealed that teaching by YouTube video was effective to enrich student’s vocabulary at the eighth-grade students of SMP Negeri 3 Palembang.